Differential mutation spectrum and immune landscape in African Americans versus Whites: A possible determinant to health disparity in head and neck cancer. (1st November 2020) - Chaudhary, Sanjib; Dam, Vi; Ganguly, Koelina; Sharma, Sunandini; Atri, Pranita; Chirravuri-Venkata, Ramakanth; Cox, Jesse L.; Sayed, Zafar; Jones, Dwight T.; Ganti, Apar K.; Ghersi, Dario; Macha, Muzafar A.; et al.
Abstract: African Americans (AA) with Head and Neck Squamous Cell Carcinoma (HNSCC) have a worse disease prognosis than White patients despite adjusting for socio-economic factors, suggesting the potential biological contribution. Therefore, we investigated the genomic and immunological components that drive the differential tumor biology among race. We utilized the cancer genome atlas and cancer digital archive of HNSCC patients (1992–2013) for our study. We found that AA patients with HNSCC had a higher frequency of mutation compared to Whites in the key driver genes— P53, FAT1, CASP8 and HRAS. AA tumors also exhibited lower intratumoral infiltration of effector immune cells (CD8 +, γδT, resting memory CD4 + and activated memory CD4 + T cells) with shorter survival than Whites. Unsupervised hierarchical clustering of differentially expressed genes demonstrated distinct gene clusters between AA and White patients with unique signaling pathway enrichments. Connectivity map analysis identified drugs (Neratinib and Selumetinib) that target aberrant PI3K/RAS/MEK signaling and may reduce racial disparity in therapy response. Highlights: Inherent biological factors drive disparate outcomes in HNSCC. African American with HNSCC have poor disease prognosis. African American with HNSCC harbor distinct mutational spectrum with low immune infiltration. CMAP based identification of four novel drugs may reduce disparate in therapy response.